New Tail Probability Type Concentration Inequalities and Complete Convergence for WOD Random Variables - Zoubeyr Kaddour, Abderrahmane Belguerna, Samir Benaissa, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The goal of this paper is to obtain some concentration in equalities for unbounded Widely Orthant Dependent (WOD) random variables. Then we will use this inequality for establishing the almost complete convergence for a sequence of widely dependent random variables (WOD).